Screening Potential CO₂ Storage Reservoirs Basin Using Petrophysical Evaluation: Case Study in Field X, Central Sumatra Basin - Charissa, Aurell Alyya; Abdillah, Hanif Ridho; Handoyo, Handoyo; Samosir, Sondang (Jurnal Phi: Kurnal Pendidikan Fisika & Terapan, 2026)
This study was conducted to evaluate the feasibility of the Menggala Formation in the Central Sumatra Basin as a potential Carbon Capture and Storage (CCS) reservoir candidate based on the analysis of key petrophysical parameters. Well log analysis was carried out by determining reservoir depth, effective thickness, effective porosity, and Net-to-Gross (NTG) as indicators of reservoir suitability. The results show that the reservoir depth ranges from 1662.48 to 1805.14 m, with an average of 1705.108 m, thereby meeting the requirement for CO₂ storage under supercritical conditions. The average effective porosity of 15.54%, effective thickness of 23.38 m, and NTG value of 0.595 indicate adequate reservoir quality at the initial screening stage. Although lateral variation exists among the wells, the Menggala Formation generally meets the criteria as a potential CO₂ injection site. However, further studies, including volumetric storage capacity estimation and caprock (seal) integrity evaluation, are required to ensure long-term reservoir feasibility.